Investigating the Necessity of Using Intelligent Marketing Information System in Iran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, we tend to develop a suitable system for intelligent market management in the insurance industry. This system is used in all companies and institutions in Iran. This system can play an important role for market research and market evaluation. A mixed study was conducted through meta-analysis and by a questionnaire and the results were analyzed. The variables were obtained and the problem was determined through interviews with exper:ts of the insurance industry in a few sessions. The results were evaluated through review of more than 100 articles; by distributing the questionnaire and analyzing it, we achieved significant specifications in the model of an intelligent system in Iran. In this study, we obtained the proper model of an intelligent system and needs of managers in evaluating management criteria in the insurance industry. The necessity of a database and using internet data and importance of an input data analysis system and collected data were confirmed.: Finally, we reached the position of a suitable model for Iranian companies, especially the insurance industry. The need to use the analyzed data was identified for market research and design of appropriate packages in management of insurance companies.